Mulethi (licorice): real but unrecognised hazards of superstitions in mothers: a case report - Lohiya, Sham; Akhil, Chitturi V. S.; Ganvir, Shubhangi P.; Vagha, Jayant (International Journal of Contemporary Pediatrics, 2022)
Licorice extract has long been known as a natural sweetener and thirst reliever. Many people who take large amounts and are prone to complications overestimate its nutritional benefits. Glycyrrhetic acid, the active metabolite in licorice, inhibits 11-ß-hydroxysteroid dehydrogenase enzyme type 2 causing increased cortisol levels and hypernatremia, hypokalemia. In this case report, we ensure a holistic study of licorice, as well as the documented side effects of excessive consumption. The study emphasises the necessity of looking into dietary habits and herbal medicines that are utilised around the world based on cultural and habitual grounds rather than scientific data. Not many case reports are available on this particular aspect of licorice consumption and its unknown adverse effects. We anticipate that our review will serve as a deterrent to parents’s superstitious beliefs on the benefits of licorice consumption.